PENGUATAN AKUNTABILITAS PENGELOLAAN PENDAPATAN ASLI DESA SEBAGAI UPAYA PENCEGAHAN PENYALAHGUNAAN WEWENANG DI DESA PULAU RAJAK KABUPATEN BANYUASIN - Derry Angling Kesuma; Liza Deshaini; Bambang Sugianto; Austin Al Haris; Muhamad Yossi Agustian (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This community service program was conducted to strengthen the understanding of village officials in Pulau Rajak Village, Banyuasin Regency, regarding the importance of accountability in managing Village Original Revenue as an effort to prevent abuse of authority. Village Original Revenue is one of the sources of village income, which may derive from village business activities, village assets, community self-help and participation, mutual cooperation, and other legitimate village revenues as regulated under Article 72 of Law Number 6 of 2014 concerning Villages. Village financial management must also be carried out based on the principles of transparency, accountability, participation, orderliness, and budget discipline. This program aims to provide legal education to village officials regarding the governance of Village Original Revenue, recording and reporting mechanisms, internal supervision, and legal risks related to abuse of authority in village financial management. The methods used include legal counseling, interactive discussion, risk mapping, and evaluation of participants’ understanding. The results show an increase in participants’ understanding of accountability principles, the importance of administrative documentation, and the need for prudence in managing Village Original Revenue to prevent administrative and legal problems. This activity is expected to encourage more transparent, accountable, and integrity-based management of Village Original Revenue in Pulau Rajak Village.